Strategic business models field lab: analysis of the peer-to-peer business model in the Ota accommodation industry- recommendation: strategic actions to improve competitiveness and sustainability - Resende, Francisca Bélico de Velasco Neno de (2022)
Despite the harsh impact of the COVID-19 pandemic, the OTA Accommodation industry remains a growing and diverse environment. Utilizing Business Model Analysis as a guiding framework, this Field Lab Report provides insights into the evolution and variation of OTA Accommodation business models. The focus is then narrowed on the Peer-to-Peer Accommodation Model with an analysis of its main components, advantages, and vulnerabilities. Three detailed recommendations are ultimately proposed to strategically optimize this business model and address innovation opportunities. In this individual section, the proposed recommendation tackles identified vulnerabilities of the P2P business model, with focus on negative externalities in local communities, and the regulatory context. Additionally, a set of actions is analyzed to increase the sustainability of this business model.